Study on seismic behavior of CHS T-joints under quasi-static cyclic in-plane bending. (April 2023) - Zhao, Bida; Li, Fulong; Liu, Chengqing; Huang, Zhenzhe; Zheng, Yayi
Abstract: This paper aim to study the in-plane flexural behaviors of circular hollow section (CHS) T -joints by quasi-static cyclic loading test and finite element (FE) analysis. Two specimens under cyclic in-plane bending (IPB) were carried out to investigate the effect of the brace-to-chord diameter ratios (a key parameter for the CHS joints and denoted as β ) on the seismic behaviors of the T -joints. Moreover, finite element (FE) analysis were performed to study the effect of β, γ (another key parameter for the joints with name of the chord radius-to-thickness ratio) and the chord axial pressure on the in-plane flexural behavior of the T -joints. Test results showed that both two specimens failed in tearing of the chord wall at the heat-affected zone (WHAZ), and both two specimens exhibit good ductility and energy dissipation behavior. Both specimens mainly rely on the plastic development of the chord wall near brace/chord intersection and the crack propagation (after cracking) to dissipate energy input by the earthquake. Test results also found that the current specification conservatively predict the in-plane flexural strength of the T -joints (about 20 %–30 %), especially for the joints with larger β . Test and FE results also show that the increase of β (or the decrease of γ ) will effectively improve the flexural strength, energy dissipation capacity and ductility ratio. The results also shows that chord pressure stress will adversely affect the in-plane flexural behavior of the T -joints, especially when the stress is larger than 0.6 times of the chord yield strength. A FE parametric study was performed to investigate the effect of β on the force transmission characteristics of the T -joints under IPB, and the force transmission characteristics in elastic state was further interpreted by a simple semi-circular arch analytical model.